Pengaruh Media Animasi English Singsing dalam Pengenalan Kosakata Bahasa Inggris bagi Anak Usia Dini - Putri, Dwi Miranti; Ismet, Syahrul (Asian Journal of Early Childhood and Elementary Education, 2025)
The study aims to analyze the fact that the teacher only introduces english vocabulary only through by the singing method, which in reality only teach basic vocabulary definitions. The purpose of this study was to determine how influenced the english singsing animation media are at teaching english vocabulary of group B children at Taman Kanak-kanak Kartika 1-63 in Padang City. This kind of study uses a one-group pretest-posttest design model and is quantitative with a quasi-experimental design. Data analysis compares two groups using uji-t. Based on the sig value (2-tailed) it is 0.004<0.05. Thus, english singsing animation media affect kid english vocabulary early age.